Penyuluhan: Meningkatkan Perilaku Penanganan Hipertensi di Masyarakat : Education: Improving Hypertension Management Behavior in the Community - Mahyuvi, Tata; Prasetyo, Joko; Puspitasari, Yenny; Amar, Munif; Kristiya , Dony (Chakra Brahmanda Lentera Institute, 2023)
Hypertension is a non-communicable disease which is a very serious health problem and the main cause of death worldwide. Hypertension can be called the silent killer because there are no signs or symptoms that appear and cannot be seen from the outside, but if it is not controlled properly it is very risky to cause degenerative diseases and various complications that arise. This community service aims to increase knowledge of how to treat hypertension in the community by providing education to the community. This community service activity was carried out on Tuesday, March 21, 2023 at Mitra Medika Bondowoso Hospital using lecture and discussion methods. with 25 participants to find out how the patient's knowledge about hypertension. How to do this to find out knowledge related to behavior to prevent and control hypertension used in community service activities is to ask and answer directly to patients. Before being given education in the form of health counseling about asthma, participants were asked questions and answers and after the material was delivered, questions and answers were held to observe participant's; knowledge regarding hypertension.